PENGARUH ARUS KAS BEBAS, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KEBIJAKAN UTANG TERHADAP KEBIJAKAN DIVIDEN PADA EMITEN MANUFAKTUR DI BURSA EFEK INDONESIA - Nazariah Nazariah (Jurnal Telaah dan Riset Akuntansi, 2014)
This research is aimed to examine the effect of free cash flow, managerial ownership, institutional ownership and debt policy toward dividend policy. The research type by using census method.The target population of thisresearch is listed companies fromthe manufacturing sector at the Indonesia Stock Exchange. After being selected, there are 11 companies as target population. Because this research is done for four years, the total observations are 44. This research was analyzed by using multiple linear regression analysis. The simultaneously testing results show that  free cash flow, managerial ownership, institutional ownership, and debt policy affect dividend policy. The partially test results show that only variable of free cash flow has negative effect on dividend policy, while the managerial ownership variables, institutional ownership, and debt policy has positive effect on dividend policy. Keywords : Free cash flow, Managerial ownership, Institutional ownership, Debt policy, Dividend policy.